MP-2 Theileriosis Prevalence On The Cattle In District Gorontalo - Muhammad Sayuti; Tri Ananda Erwin Nugroho (Hemera Zoa, 2018)
This study aims to study the disease of protozoan blood in cattle in Gorontalo regency caused by Theileria sp .. Some protozoa of blood that infect cows include Theileria sp., Trypanosoma sp., And Babesia sp. The presence of protozoa will lead to anemia, growth disorders, reproductive disorders and death. In general, the protozoa of this blood will hamper the livestock business and result in economic losses for farmers.The sample of cow's blood in Gorontalo Regency is the object studied. The samples taken were 158 cows obtained through the slovin equation with 93% accuracy. Samples were taken at the farmers' level belonging to livestock groups and not belonging to livestock groups in Kabupaten Gorontalo. The study was conducted by examining cow blood memelaluimetode blood thin scalp examination using binocular microscope with 1000 magnification. Data analysis done descriptively. The results obtained found 32.5% of cattle suffering from Theilleriosis